Unveiling the ecological significance of phosphorus fractions in shaping bacterial and archaeal beta diversity in mesotrophic lakes - Yuan, Haijun; Zhang, Runyu; Li, Qiuxing; Han, Qiao; Lu, Qiping; Wu, Jing (Frontiers in Microbiology, 2023)
Both community variation and phosphorus (P) fractions have been extensively studied in aquatic ecosystems, but how P fractions affect the mechanism underlying microbial beta diversity remains elusive, especially in sediment cores. To compare the depth-related patterns of bacterial and archaeal beta diversity, we obtained two sediment cores from mesotrophic lakes Hongfeng Lake and Aha Lake, having historically experienced severe eutrophication. Utilizing the Baselga's framework, we partitioned bacterial and archaeal total beta diversity into two components: species turnover and nestedness, and then examined their sediment-depth patterns and the effects of P fractions on them. We found that total beta diversity, species turnover or nestedness consistently increased with deeper sediment layers regarding bacteria and archaea. Notably, there were parallel patterns between bacteria and archaea for total beta diversity and species turnover, which is largely underlain by equivalent processes such as environmental selection. For both microbial taxa, total beta diversity and species turnover were primarily constrained by metal oxide-bound inorganic P (NaOH-Pi) and sediment total phosphorus (STP) in Hongfeng Lake, while largely affected by reductant-soluble total P or calciumbound inorganic P in Aha Lake. Moreover, NaOH-Pi and STP could influence bacterial total beta diversity by driving species nestedness in Hongfeng Lake. The joint effects of organic P (Po), inorganic P (Pi) and total P fractions indicated that P fractions are important to bacterial and archaeal beta diversity. Compared to Po fractions, Pi fractions had greater pure effects on bacterial beta diversity. Intriguingly, for total beta diversity and species turnover, archaea rather than bacteria are wellexplained by Po fractions in both lakes, implying that the archaeal community may be involved in Po mineralization. Overall, our study reveals the importance of P fractions to the mechanism underlying bacterial and archaeal beta diversity in sediments, and provides theoretical underpinnings for controlling P sources in biodiversity conservation.